Low‐ and high‐risk human papillomavirus genotype infections in intra‐anal warts in HIV‐positive men who have sex with men. (6th July 2016) - Siegenbeek van Heukelom, M.L.; Richel, O.; de Vries, H.J.C.; van de Sandt, M.M.; Beck, S.; van den Munckhof, H.A.M.; Pirog, E.C.; de Koning, M.N.C.; Prins, J.M.; Quint, K.D.
Summary: Background: Anogenital warts are often presumed to represent nondysplastic or low‐grade anal intraepithelial neoplasia (LGAIN). We previously demonstrated that up to 20% of intra‐anal warts in HIV‐positive men who have sex with men (MSM) contain regions of high‐grade AIN (HGAIN). Objectives: To determine the causative human papillomavirus (HPV) types of low‐ and high‐ grade dysplastic areas in warts from HIV‐positive MSM. Methods: A total of 42 intra‐anal warts from 41 HIV‐positive MSM were graded as nondysplastic, LGAIN or HGAIN. Whole‐tissue sections (WTS) were analysed with the SPF10 polymerase chain reaction/LiPA25 HPV genotyping system. If the WTS contained multiple HPV types, dysplastic regions were isolated by laser capture microdissection (LCM) for HPV genotyping. Results: Overall, 38 of 42 (91%) WTS tested positive for HPV DNA. Of these, 23 (61%) contained a single HPV type and 15 (39%) contained multiple HPV types. All LCM‐selected regions contained no more than one HPV type. Ten of 42 (24%) WTS contained HGAIN disease, of which six (60%) were associated with a high‐risk HPV (hrHPV) genotype. Twenty‐three of 42 WTS contained LGAIN disease, of which two (9%) were associated with hrHPV. AIN lesions containing hrHPV types were identified using p16 staining. Conclusions: LGAIN lesions can be caused by high‐risk HPV genotypes and vice versa. We therefore recommend routine follow‐up and treatment of all dysplastic intra‐anal warts for HIV‐positive MSM. Abstract : What is already known about this topic? Intra‐anal warts in HIV‐positive men who have sex with men can contain regions of high‐grade anal intraepithelial neoplasia (AIN). Individual components of high‐grade AIN are caused by single human papillomavirus (HPV) genotype infections. What does this study add? Low‐grade AIN lesions can be caused by high‐risk HPV genotypes and vice versa. Positive p16 immunostaining identifies AIN lesions caused by high‐risk HPV types. Linked Comment: Kreuter and Wieland. Br J Dermatol 2016;175 :672–673 .